Frequency of Staff Development Programs and Teachers’ Job Performance in Kwara State Primary Schools, Nigeria - Oluwatoyin, Fashiku Christopher; Jumoke, Atere Kafayat; Ayowole, Agbaje Ezekiel (ETDC: Indonesian Journal of Research and Educational Review, 2023)
The study adopted a descriptive survey research design. The population of the study consisted of 14,206 public primary school teachers and 1,406 head teachers in the senatorial districts of Kwara State. The sample for the study comprised 440 respondents selected using a multistage sampling procedure. A self-designed, validated research instrument titled “Staff Development and Teachers Job Performance” (SDTJP) was used to collect data for the study. The reliability of the instrument was ensured with a coefficient index of 0.77. The collected data were analyzed using percentage scores and regression analysis. The result shows that the frequency of conducting the program for the Kwara State primary school teachers was once every session for some programs (88.4% and termly for others (68.2%) in Kwara State primary schools. Developmental programs significantly influenced staff job performance in the schools, 58.9% (Adj. R2 =.589). The study concluded that the development programs for teachers in Kwara state primary schools were carried out termly, while some other ones came up once in a session. It was also discovered that developmental programs significantly influenced staff job performance in the state primary schools. It was recommended that the government endeavor to add conferences as part of the professional development programs made available for primary school teachers in Kwara State to enhance their pedagogic skills and competence towards meeting the expectations of the general public.